DAMPAK MEDIA SOSIAL TERHADAP KESEJAHTERAAN MENTAL REMAJA: PERSPEKTIF PEKERJA SOSIAL SEKOLAH - HULISELAN, DOAN VEBRIANDI; SUPULATU, CHRISTI; LEMOSOL, NATALIS; LATUHERU, DESTRY; PITNA, VENTY (Fakultas Ilmu Sosial dan Ilmu Politik, 2021)
The increasingly intensive use of social media among adolescents has generated various impacts on their mental health, positioning school social workers as frontline responders in addressing these issues. This study aims to analyze the impact of social media on adolescent mental health from the perspective of school social workers through a systematic literature review approach. Using the PRISMA protocol, 48 articles published between 2019-2024 were systematically analyzed. The results indicate that adolescents spend an average of 6.5 hours daily on social media, with significant mental health impacts including anxiety (85%), depression (78%), and sleep disorders (72%). School social workers face major challenges in digital competency limitations (78%) and work overload (72%). Digital literacy programs show the highest effectiveness rate (85%) in interventions. This study recommends developing social workers' digital competencies, restructuring hybrid service models, and strengthening multi-stakeholder collaboration. These findings contribute significantly to the development of school social work practice in the digital era.